Duck HMGB2 Mediates Signaling Pathways in the Innate Immunity of Hosts Against Viral Infections - Zhang, Tingting; Zhang, Xinyue; Sun, Zhenhong; Liu, Gen; Hou, Xiaolan; Wei, Liangmeng (Frontiers in Immunology, 2020)
High-mobility group box 2 (HMGB2) belongs to the HMG-box family that participates in a variety of biologic processes. Recent studies have suggested that HMGB2 plays an important role in the innate immunity of fish. Cherry Valley duck is the main duck bred for meat consumption in China, but there is limited research available on the impact of duck HMGB2 (duHMGB2) in antiviral innate immunity. Here, duHMGB2 genes were first cloned and analyzed from the spleen of Cherry Valley ducks. We show that duHMGB2 is widely distributed in most tissues of healthy ducks, and duHMGB2 was differentially expressed in three organs (the spleen, brain, and lung) of ducks during different viral infections. duHMGB2 is mainly expressed in the nucleus of duck embryo fibroblast (DEF) cells. However, duHMGB2 is released into the cytoplasm after viral infection. DuHMGB2 induced expression of several genes thatregulate the immune response. Moreover, duHMGB2 activated and upregulatede transcription factor NF-κB promoter activity. We also used single gene manipulations (knockout or overexpression) to confirm that duHMGB2 can inhibit the replication of duck plague virus, duck Tembusu virus, and the novel duck reovirus in DEF cells. These data show that duHMGB2 can activate the antiviral innate immunity of the host. Thus, duHMGB2 may be considered an immune adjuvant against infectious diseases in duck.